A case report of delayed treatment of acute exertional osteofascial compartment syndrome in the anterior compartment of the calf. Issue 52 (30th December 2022) - Liu, Shiwei; Wang, Congcong; Song, Wenjing; Wang, Jun; Zhao, Shibo
Abstract : Rationale: Acute exertional osteofascial compartment syndrome (OCS) is a rare cause of lower-leg pain and is often associated with delayed diagnosis, which can lead to irreversible muscle and nerve damage. Patient concerns: A 23-year-old man presented with acute-onset anterior calf pain and ankle dorsiflexion after hiking. Diagnosis: The patient's pain was initially diagnosed as muscle strain at a county hospital, but was eventually diagnosed as OCS at our hospital 8 days after the injury. This case presents several challenges in the diagnosis and treatment phases. Interventions: Three surgeries were performed in total. On the day after admission (9 days after injury), fasciotomy was performed, followed by vacuum sealing drainage (VSD). Six days after the first surgery, necrotic muscle debridement was performed and VSD was reperformed. Ten days after the second surgery, the covering foam material was removed and the incision was sutured. Outcomes: Satisfactory postoperative results were achieved. The erythrocyte sedimentation rate, C-reactive protein level, and white blood cell count were within normal ranges. The skin healed well, and nerve damage and muscle strength improved significantly 3 months after surgery. Lessons: OCS in the absence of trauma or fracture is rare, but treatment delays can have devastating consequences. Acute nontraumatic OCS requires prompt diagnosis and surgical intervention to prevent adverse outcomes. VSD is an effective surgical treatment for this disease.